2016
DOI: 10.2217/rme-2016-0059
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Cell Sheet Engineering in the Vascularization of Tissue Regeneration

Abstract: Scaffold-free cell sheet engineering (CSE) is a new technology to regenerate injured or damaged tissues, which has shown promising potential in tissue regeneration. CSE uses a thermosensitive surface to form a dense cell sheet that can be detached when temperature decreases. The detached cell sheet can be stacked on top of one another according to the thickness of cell sheet for the specific tissue regeneration application. One of the key challenges of tissue engineering is vascularization. CSE technique provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 85 publications
1
50
0
Order By: Relevance
“…Similar studies were also carried out on adipose stem cells (ASCs): the seeding of ASCs onto a microvascular flap, in combination with beta-tricalcium phosphate (b-TCP) and BMP-2 showed promising results in the treatment of large and complicate jaw defects, up to 8 months after the graft implantation [13].…”
Section: The Role Of Growth Factors (Gfs) and Mesenchymal Stem Cells mentioning
confidence: 87%
“…Similar studies were also carried out on adipose stem cells (ASCs): the seeding of ASCs onto a microvascular flap, in combination with beta-tricalcium phosphate (b-TCP) and BMP-2 showed promising results in the treatment of large and complicate jaw defects, up to 8 months after the graft implantation [13].…”
Section: The Role Of Growth Factors (Gfs) and Mesenchymal Stem Cells mentioning
confidence: 87%
“…After a complete cell sheet is formed, lowering the temperature to 32 °C returns the PNIPAM to a hydrophilic state that rapidly absorbs water and swells, allowing the monolayer cell sheet to detach . Compared with cell harvesting methods that use proteolytic enzymes such as trypsin and dispase, the use of temperature‐responsive culture dishes maintains intact cell junctions and ECM which promotes cell communications . Cells can also be cultured on top of polymer sheets produced by other techniques such as electrospinning and molding to form cell‐polymer sheets.…”
Section: Cell‐based Techniquesmentioning
confidence: 99%
“…Hepatocyte‐based cell sheet stacking has been used to create small liver tissues . Hepatocytes are high oxygen demanding cells and hence blood supply is crucial . EC and hepatocytes sheets stacked in an EC‐hepatocytes‐EC structure showed increased hepatocyte layer thickness, ECM secretion, and hepatocyte‐specific functions compared to bi‐layer or hepatocyte‐only constructs .…”
Section: Cell‐based Techniquesmentioning
confidence: 99%
“…Cell sheet engineering uses a thermosensitive surface to form a dense cell sheet that can be detached when temperature decrease and can then be stacked on top of one another according to the thickness of cell sheet for the specific tissue regeneration application. This technique should provide excellent microenvironment for vascularization, since an intact cell matrix will be maintained for angiogenesis [14]. In addition, a study has shown that mesenchymal stem cells that were cultured as cell sheets and delivered as a scaffold-free cell sheet injection results in bone formation [15].…”
Section: Clinical Backgroundmentioning
confidence: 99%